Establishment of muscle mass-based indications for the cystatin C test in renal function evaluation - Yim, Jisook; Son, Nak-Hoon; Kim, Kyoung Min; Yoon, Dukyong; Cho, Yonggeun; Kyong, Taeyoung; Moon, Ja-Young; Yi, Tae Im; Lee, Sang-Guk; Park, Yongjung; Lee, Jung Joo; Kim, Kyung-Ah; et al. (Frontiers in Medicine, 2022)
Background We aimed to suggest muscle mass-based criteria for using of the cystatin C test for the accurate estimated glomerular filtration rate (eGFR). Materials and methods We recruited 138 Korean subjects and evaluated eGFRcr (derived from Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) based on creatinine) was compared to eGFRcys based on cystatin C as the reference value. The skeletal muscle mass index (SMI) by bioelectrical impedance analysis (BIA) was used as representative of muscle mass. Calf circumference (CC) was also evaluated. We defined the patients by eGFRcr as those with values of eGFRcr ≥ 60 mL/min/1.73 m2 but eGFRcys < 60 mL/min/1.73 m2 as the detection of hidden renal impairment (DHRI). Cut-off values were determined based on muscle mass for the cases of DHRI suggesting the criteria of cystatin C test in renal function evaluation. Results We confirmed significant negative correlation between %difference of eGFRcr from eGFRcys and SMI (r, −0.592 for male, −0.484 for female) or CC (r, −0.646 for male, −0.351 for female). SMI of 7.3 kg/m2 for males and 5.7 kg/m2 for females were suggested to be significant cutoffs for indication of cystatin C test. We also suggested CC would be valuable for cystatin C indication. Conclusion We suggested the muscle mass-based objective criteria relating to SMI and CC that would indicate the use of cystatin C to evaluate renal function test in sarcopenic cases. Our results highlight the importance of muscle mass-based selection of renal function.